SYNTHESIS AND CHARACTERIZATION OF MAGNETITE NANOMATERIALS IN TIANYAR IRON SAND USING CO-PRECIPITATION METHOD - Kristina, Ni Putu Devi; Arjana, I Gede; Yasa, Putu (Indonesian Physical Review, 2024)
In the current era of scientific and technological progress, nanomaterials have emerged as a deeply fascinating and significant field of research. This paper presents a case study on the synthesis and characterization of Fe₃O₄ nanomaterials derived from the iron sand of the Tianyar, utilizing the co-precipitation method with modifications made to the pH values during synthesis. The research encompasses three primary stages: extraction of iron sand, synthesis of Fe3O4 nanomaterials, and subsequent characterization of these nanomaterials. The iron sand extraction phase involved passing it through a permanent magnet ten times to remove impurities. Subsequent synthesis produced a dark black magnetite nanomaterial powder displaying magnetic properties, rendering it responsive to magnet attraction. Analysis of these nanomaterials using X-ray diffraction (XRD) unveiled discernible peaks in the diffraction pattern, suggesting that the magnetite nanomaterials possess a cubic crystal structure. The size of the Fe3O4 nanomaterials decreases as the pH of precipitation increases, with respective sizes of approximately 18.00 nm for pH 9, 14.69 nm for pH 10, and around 13.68 nm for pH 11, as determined using Scherrer’s formula. The lattice parameters observed for samples synthesized at pH 9, 10, and 11 are sequentially measured as a = 8.59 Å, 8.81 Å, and 8.80 Å. Analysis using SEM-EDS revealed that the sample morphology appears rough, with evidence of particle agglomeration leading to uneven particle distribution. There are additional trace elements present, including C, Al, S, Ti, and Cl, albeit in smaller quantities. Nevertheless, the primary elements crucial for forming Fe3O4 nanomaterials, namely Fe and O, exhibit the highest percentages in composition analysis.